(E) zapis na sąd polubowny - Czerwińska, Berenika (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Arbitration clause is an institution governed by the Code of Civil Procedure, which is designed to accelerate, facilitate and reduce the costs of cooperation between parties, particularly in international trade matters. The purpose of this article is to discuss the legal nature of the arbitration agreement, with particular regard to the mandatory form of its conclusion and the consequences of their failure to perform. It also discusses the possibility of making such a record by means of electronic communication as well as an electronic signature
Keywords: sąd polubowny; podpis kwalifikowany; środki komunikacji elektronicznej